Computer-Integrated Monitoring Technology with Support-Decision of Unauthorized Disturbance of Methane Sensor Functioning for Coal Mines - Oleksandr Vovna; Hanna Kaydash; Leszek Rutkowski; Іvan Sakhno; Іvan Laktionov; Maryna Kabanets; Sergey Zozulya (Journal of Control Science and Engineering)
In longwall coal mining, high methane concentrations pose a challenge. Cyber-physical air and gas protection systems ensure operational safety. However, safeguarding methane sensors from unauthorized interference is a key issue. This research aims to develop an intelligent method for detecting disturbances in methane sensor operation, preventing mining emergencies. The methodological basis for achieving the research goal is an integrated approach using proven scientific methods: analysis of existing scientific and practical results; computer modeling, development, and creation of prototypes of computer-integrated stands for studying the processes of external influence on measurement results. The primary advantage of the proposed method is the software implementation of the specified approach on the existing computer-integrated modules and sensor hardware platform. This allows for the identification of unregulated modes of operation without the need for hardware redundancy during the implementation of measurement modules for information processing in cyber-physical systems. The structure of computer-aided monitoring with decision support has been substantiated and developed, which implements the mathematical apparatus of the proposed method for detecting unauthorized interference with sensor operation modes. The implementation of the developed method of detecting unauthorized interference in the regulated mode of the methane concentration sensor made it possible to detect such interference from 15 seconds, if the concentration is more than 1.45%, to 20 seconds during the action of the minimum methane concentration of 0.24%. The specified time interval from 15 to 20 seconds is approximately equal to the time constant of the transition process, which varies depending on the degree of tightness of its sensitive element.